RECONCILING RENEWABLE PORTFOLIO STANDARDS AND FEED-IN TARIFFS (Utah Environmental Law Review, 2012)
This Article questions the customary logic on renewable energy policy design. It asks whether renewable portfolio standards and feed-in tariffs really must be mutually exclusive paths to a more sustainable energy future or if, instead, there is an opportunity to blend these two policy devices. The Article concludes the latter. Renewable portfolio standards and feed-in tariffs complement—not foreclose—each other. Indeed, by using renewable portfolio standards and feed-in tariffs in tandem, jurisdictions may be able to harness regulatory synergies that would not otherwise exist. Renewable portfolio standards offer something that feed-in tariffs do not. They focus on the quantity of renewable power provided. By consequence, they provide aspirational clarity and regulatory accountability, because the legal goals they set are comparatively transparent. Feed-in tariffs, too, add something that portfolio standards cannot. They center on price. By setting an upfront cost of compliance and guaranteeing the purchase of renewables-based electricity, feed-in tariffs offer the kind of market certainty that investors crave. Thus, while evidence is still emerging on the question of whether RPSs or FITs are better at encouraging renewables deployment, that debate is unnecessary. With sufficient political will, RPSs and FITs can be harnessed together in a way that should be more effective than using either alone. This Article seeks to provide a road map for how the potential regulatory symbiosis between feed-in tariffs and renewable portfolio standards might be realized. Broadly, the renewable portfolio standard might be seen as a planning procedure and the feed-in tariff as its implementing device. Renewable portfolio standards embody the destination we are trying to reach on our collective energy landscape; the feed-in tariff is the engine that can drive us there. More concretely, the RPS and feed-in tariff could be used together by having the RPS set the renewable energy target desired and using the FIT as the primary incentive for greater RE production.